2007
DOI: 10.1002/dneu.20364
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of extracellular and intracellular calcium sources to basal transmission and long‐term potentiation in the sympathetic ganglion of the rat

Abstract: Calcium involved in basal ganglionic transmission and long-term potentiation (LTP) can arise either by influx from the extracellular medium or release from intracellular stores. No attempts have yet been made to concurrently explore the contributions of extracellular and intracellular Ca2+ to basal ganglionic transmission or LTP. Here, we investigate this subject using the superior cervical ganglion of the rat. To explore the extracellular Ca2+ contribution, we evaluated basal transmission and LTP at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In addition to NMDARs, other sources of Ca 2ϩ may also contribute to the increase in postsynaptic Ca 2ϩ seen in this pairing-induced potentiation, such as voltage-gated Ca 2ϩ channels (VGCCs) and release of Ca 2ϩ from internal stores, the latter potentially mediated by either IP 3 or ryanodine receptors (Balschun et al 1999;Kapur et al 1998;Vargas et al 2007). To test whether LTP requires VGCC activation, nimodipine (10 M) was superfused during administration of the pairing protocol.…”
Section: Pairing-induced Potentiation Requires An Increase In Postsynmentioning
confidence: 99%
“…In addition to NMDARs, other sources of Ca 2ϩ may also contribute to the increase in postsynaptic Ca 2ϩ seen in this pairing-induced potentiation, such as voltage-gated Ca 2ϩ channels (VGCCs) and release of Ca 2ϩ from internal stores, the latter potentially mediated by either IP 3 or ryanodine receptors (Balschun et al 1999;Kapur et al 1998;Vargas et al 2007). To test whether LTP requires VGCC activation, nimodipine (10 M) was superfused during administration of the pairing protocol.…”
Section: Pairing-induced Potentiation Requires An Increase In Postsynmentioning
confidence: 99%
“…We can speculate that the elevated postsynaptic expression of TfR in PAE animals masks the presynaptic effect because it regulates the iron concentration in the synaptic cleft. However, deferiprone incubation slightly decreased AMPAR synaptic transmission in control as well in PAE animals denoting that the mechanism involving basal synaptic transmission is a complex process, therefore we cannot discard that other mechanisms are affecting by Iron, such as presynaptic and postsynaptic events (Vargas et al, 2007; Fioravante and Regehr, 2011; Ramaswami et al, 2016) and the complex regulation by astrocytes (Navarrete and Araque, 2011; Panatier et al, 2011). Additional studies are necessary to determine which is the putative mechanism.…”
Section: Discussionmentioning
confidence: 91%
“…Raymond and Redman (2006) reported that the induction of short‐lasting LTP required activation of RyRs, which selectively increased Ca 2+ in hippocampal synaptic spines. Furthermore, a study showed that LTP expression not only requires more Ca 2+ entry but is also dependent on Ca 2+ release from intracellular stores in the superior cervical ganglion (Vargas et al, 2007). Similarly, the ryanodine‐sensitive intracellular calcium store was involved in the induction of spinal synaptic LTP (Drdla et al, 2009).…”
Section: Discussionmentioning
confidence: 99%